Heart rate during training and competition for long-distance running - Lambert, M. I.; Mbambo, Z. H.; Clair Gibson, A. (Journal of Sports Sciences, 1998)
Heart rate monitors are used widely by scientists, coaches and sports participants to monitor heart rate during physical activity. Although there are data that show that heart rate monitors measure heart rate accurately during a range of physical activities, there is less consensus on the interpretation of heart rate data. The day-to-day variation in heart rate under controlled submaximal exercise conditions is approximately 6 beats min −1, which is generally less than the decrease in the submaximal heart rate that results from endurance training. A bout of exercise that causes moderate dehydration can affect heart rate during submaximal exercise. It has been estimated that, for every 1% loss in body weight due to dehydration, heart rate increases by 7 beats min −1. During a 10-km race, the heart rate is approximately 20 beats min −1 higher at racing pace compared to the heart rate at the same running speed under non-competitive conditions. In conclusion, heart rate monitors measure heart rate accurately under diverse conditions, and have the potential to be regarded as `ergogenic aids'. However, further scientific studies are needed before the heart rate data can be interpreted accurately and used to improve long-distance running performance.